Early Extubation and Fast-Track Management of Off-Pump Cardiac Patients in the Intensive Care Unit. (June 2015) - Bainbridge, Daniel; Cheng, Davy C.
Off-pump surgery was the original approach to treating patients with cardiac disease in the era before cardiopulmonary bypass. With the advent and refinement of cardiopulmonary bypass, the use of this technique fell out of favor and was quickly surpassed by on-pump techniques. However, the limitations of bypass surgery, especially for coronary artery bypass procedures, was still significant, leading to renewed interest in this technique. Postoperative care for off-pump coronary artery bypass (OPCAB) surgery presents both a challenge and opportunity to the intensivist. OPCAB patients can be treated in a fast-track manner allowing rapid recovery and early extubation and discharge from the intensive care unit. This is supported through the use of protocols that help standardize care and set expectations for the post–cardiac care team. Importantly, complications that may delay recovery including hypothermia, hypotension, and bleeding must be recognized early and treated aggressively to prevent unwanted complications and intensive care delays. Finally, care of these patients has shifted to the post-anesthesia recovery room, making knowledge of the care of these patients in the early postoperative period essential for cardiac anesthesiologists. This article will discuss the care of OPCAB patients following surgery and include approaches to managing patients who return both intubated and extubated.